Inter‐ and intra‐patient clonal and subclonal heterogeneity of chronic lymphocytic leukaemia: evidences from circulating and lymph nodal compartments. (24th November 2015) - Del Giudice, Ilaria; Marinelli, Marilisa; Wang, Jiguang; Bonina, Silvia; Messina, Monica; Chiaretti, Sabina; Ilari, Caterina; Cafforio, Luciana; Raponi, Sara; Mauro, Francesca R.; Di Maio, Valeria; De Propris, Maria S.; et al.
Summary: Whole exome sequencing and copy number aberration (CNA) analysis were performed on cells taken from peripheral blood (PB) and lymph nodes (LN) of patients with chronic lymphocytic leukaemia (CLL). Of 64 non‐silent somatic mutations, 54 (84·4%) were clonal in both compartments, 3 (4·7%) were PB‐specific and 7 (10·9%) were LN‐specific. Most of the LN‐ or PB‐specific mutations were subclonal in the other corresponding compartment (variant frequency 0·5–5·3%). Of 41 CNAs, 27 (65·8%) were shared by both compartments and 7 (17·1%) were LN‐ or PB‐specific. Overall, 6 of 9 cases (66·7%) showed genomic differences between the compartments. At subsequent relapse, Case 10, with 6 LN‐specific lesions, and Case 100, with 6 LN‐specific and 8 PB‐specific lesions, showed, in the PB, the clonal expansion of LN‐derived lesions with an adverse impact: SF3B1 mutation, BIRC3 deletion, del8(p23·3‐p11·1), del9(p24·3‐p13·1) and gain 2(p25·3‐p14). CLL shows an intra‐patient clonal heterogeneity according to the disease compartment, with both LN and PB‐specific mutations/CNAs. The LN microenvironment might contribute to the clonal selection of unfavourable lesions, as LN‐derived mutations/CNAs can appear in the PB at relapse. Abstract : This article is cited in the Editorial Comment published in issue 172:1 (http://onlinelibrary.wiley.com/doi/10.1111/bjh.13856/abstract ).